2019
DOI: 10.21203/rs.2.12655/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and attitudes towards blood donation among students of the Faculty of Applied Medical Sciences at King Abdulaziz University

Abstract: Background: This study aimed to assess knowledge about and attitude towards blood donation among students at the Faculty of Applied Medical Sciences at King Abdulaziz University. In Saudi Arabia, the shortage of blood donors is a major challenge in blood banks. This could be due to low levels of community knowledge and unfavorable attitudes. Methods: A community-based cross-sectional study was conducted between November 2017 and July 2018. A total of 350 students were randomly selected and interviewed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…However, this was contrary to findings by researchers from King Abdullah International Medical Research Centre (KAIMRC), which demonstrated that males, who answered a short survey in shopping malls in the city of Riyadh, were 50% more than female participants (Abolfotouh et al, 2014). This is also similar to the Saudi study conducted on students in the collage of applied medical sciences (Felimban et al, 2021). All these observations are more reflective of the overall population, as the demographic and attitudes of both males and females in the public arena differ compared to the privacy of their own homes, which is where Saudi females would more likely participate in a survey/questionnaire.…”
Section: Discussioncontrasting
confidence: 94%
“…However, this was contrary to findings by researchers from King Abdullah International Medical Research Centre (KAIMRC), which demonstrated that males, who answered a short survey in shopping malls in the city of Riyadh, were 50% more than female participants (Abolfotouh et al, 2014). This is also similar to the Saudi study conducted on students in the collage of applied medical sciences (Felimban et al, 2021). All these observations are more reflective of the overall population, as the demographic and attitudes of both males and females in the public arena differ compared to the privacy of their own homes, which is where Saudi females would more likely participate in a survey/questionnaire.…”
Section: Discussioncontrasting
confidence: 94%
“…From the researchers' point of view, thisage could cause a fear of needles as the main reason that the students thought caused a low rate of donating blood. These results are similarto the findings of a study conducted by Raed et al, (2021) who mentioned that the mean age of the students was around 22 years in the study conducted at King Abdulaziz University, Saudi Arabia (Felimban et al, 2019). The present study showed that more than three fifths of the studied female students' preferred receiving information regarding blood donation from doctors.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning knowledge, it was found that half of the female students at FAMS know safe blood donation and all of them mentioned appropriately the diseases could be transmitted through the blood donation. These results are similar with the study conducted by Raed et al, (2021) who mentioned that students responded yes to a question asking about the relationship between blood donations and transmitting diseases (Felimban et al, 2019). Similarly, Jacobs and Berege, (2015) found in Tanzania and areas where HIV is a common problem, that people are, typically discouraged from donating blood because they afraid getting diseases to the donors.…”
Section: Discussionsupporting
confidence: 88%
“…Fear, misunderstanding of qualifications, and lack of outreach for donor programs are the most significant obstacles to blood donation. Studies performed in the past have shown that within societies today, myths including the risk of blood-borne infections as well as anemia are contributing to low levels of blood donors [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…Still, because of unemployment and an absence of information on the topic, this critical mechanism receives inadequate attention. However, the belief that giving induces anemia or could carry illness remains in individual citizens' minds [8,9] . Owing to the shortage of modern technology for motivating voluntary blood donation, students have no real experience with it.…”
Section: Introductionmentioning
confidence: 99%